Kolaborasi Masyarakat Sipil dan Perusahaan dalam Pelaksanaan SDGs di Indonesia - Meila Riskia Fitri; Putri Rima Jauhari (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
In the history of social movements in Indonesia, civil society organisation (CSO) has taken an important role. Even since the colonial period in order to seize independence, up to this day in terms of filling the development. The global development agenda or Sustainable Development Goals (SDGs) require the role of various stakeholders, including civil society organizations and companies. The purpose of this research is to find out the form of collaboration between civil society and companies in the implementation of SDGs in Indonesia. The method used is library research. The results of this study show that Civil society Indonesia collaborates to ask the government as the person in charge of the State to implement transparent and accountable SDGs. The initiative is carried out by civil society in encouraging the role of various parties, including companies to actively participate in the implementation of SDGs in Indonesia. Among the initiatives carried out are encouraging multiparty cooperation, launching "Fiqh Zakat for SDGs", and building a multiparty platform. From the existing practices, it can be seen that there is a shifting pattern of the role of civil society, where previously faced with the State and the company, but today it is more towards collaborative work with two components in a Country.